Method for testing electrolyte resistance of aluminum-plastic film prepared by thermal lamination process

By baking and cleaning of aluminum foil and cast CPP film samples in the electrolyte with local heat sealing and quenching treatment, the thermal bonding process of lithium-ion batteries is simulated, and the electrolyte resistance performance of aluminum-plastic films is detected in advance, and the current solution is solved There are problems of long-term testing in the technology, which achieves rapid and accurate testing in the semi-finished product stage and avoids potential quality problems in battery production.

CN119164869APending Publication Date: 2024-12-20ZHIXIN BOYUAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411418198.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the process of lithium-ion battery manufacturing, the electrolyte resistance performance test of aluminum-plastic film is usually carried out after the finished product, resulting in a long detection time and the potential quality problems cannot be discovered in advance, affecting the safety and cycle life of the battery.

Method used

Test method for electrolyte resistance of aluminum plastic film prepared by thermal bonding process. Local heat sealing, quenching and quenching of aluminum foil and casting CPP film samples are carried out, and baking and cleaning are carried out in the electrolyte to measure the electrolyte treatment samples. The strip peeling force is used to simulate the thermal bonding process to detect the electrolyte resistance in advance.

Benefits of technology

This method can effectively detect the electrolyte resistance performance of aluminum-plastic films in the semi-finished product stage, avoid losses caused by quality problems after mass production, and improve the speed, efficiency and accuracy of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164869A_ABST
    Figure CN119164869A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum plastic films for lithium ion batteries, and particularly relates to a method for testing electrolyte resistance of an aluminum plastic film prepared by a thermal lamination process, which comprises the following steps: step S1, respectively cutting two passivated aluminum foil samples and a casting CPP film sample; s2, the samples are stacked according to the sequence of the aluminum foil sample, the casting CPP film sample and the aluminum foil sample, local heat sealing is carried out, and a heat-sealed sample is obtained; s3, performing quenching treatment on the heat-sealing sample, peeling off the aluminum foil sample which is not adhered to the casting CPP film sample, and then cutting a local heat-sealing area to obtain a sample strip; s4, soaking the sample table in an electrolyte, sealing, storing and baking, and then cooling and cleaning to obtain an electrolyte treated sample strip; and S5, stripping the aluminum foil sample from the casting CPP film sample in the electrolyte treated sample strip, and testing to obtain the stripping force of the electrolyte treated sample strip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum-plastic films for lithium-ion batteries, and particularly relates to a method for testing the electrolyte resistance performance of an aluminum-plastic film prepared by a thermal bonding process. Background Art

[0002] In the manufacturing process of lithium-ion batteries, aluminum-plastic film, as a key isolation material, is usually prepared by thermal bonding process (thermal bonding). This process uses co-extrusion casting to produce CPP film roll semi-finished products, and then presses the semi-finished aluminum foil rolls together with the passivated aluminum foil rolls at high temperature. This thermal bonding process can effectively improve the overall performance of aluminum-plastic film, so that it can better meet the strict requirements of lithium-ion batteries for electrolyte resistance.

[0003] However, in actual production, the electrolyte resistance performance test of aluminum-plastic film often occurs after the aluminum-plastic film is made into a finished product, and the test takes a long time. This delayed detection method makes potential quality problems not discovered until the product is mass-produced, seriously affecting the safety and cycle life of the battery.

[0004] However, due to the heat bonding process of the semi-finished aluminum-plastic film, the existing technology cannot obtain accurate electrolyte resistance performance. Therefore, how to advance the detection process of the electrolyte resistance performance of the aluminum-plastic film is a technical problem that urgently needs to be solved in this field.

[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention

[0006] The embodiments of the present disclosure at least provide a method for testing the electrolyte resistance performance of an aluminum-plastic film prepared by a thermal bonding process.

[0007] In the first aspect, the embodiments of the present disclosure provide a method for testing the electrolyte resistance of an aluminum-plastic film prepared by a thermal bonding process, comprising the following steps: step S1, cutting two passivated aluminum foil samples and a cast CPP film sample respectively; step S2, stacking the samples in the order of aluminum foil sample, cast CPP film sample, and aluminum foil sample and performing partial heat sealing to obtain a heat-sealed sample; step S3, quenching the heat-sealed sample, peeling off the aluminum foil sample that is not bonded to the cast CPP film sample, and then cutting the partial heat-sealed area to obtain a sample strip; step S4, immersing the sample table in an electrolyte, sealing, storing, and baking, and then cooling and cleaning to obtain an electrolyte-treated sample strip; and step S5, peeling off the aluminum foil sample and the cast CPP film sample in the electrolyte-treated sample strip, and testing to obtain the peeling force of the electrolyte-treated sample strip.

[0008] In an optional embodiment, the size of the aluminum foil sample and the cast CPP film sample is not less than 10 cm*10 cm.

[0009] In an optional embodiment, the aluminum foil sample includes a bright surface and a matte surface, and the bright surface of the aluminum foil sample is the contact surface with the cast CPP film sample.

[0010] In an optional embodiment, the thickness of the aluminum foil sample is 30-60 μm.

[0011] In an optional embodiment, the packaging temperature of the local heat seal is 130-250° C., the heat seal time is 2-10 s, the packaging pressure is 0.2-0.6 MPa, and the sealing head width is 10 mm.

[0012] In an optional embodiment, the rapid cooling method is to cool the heat-sealed sample between two iron plates for 5-10 s.

[0013] In an optional embodiment, the electrolyte includes any one or more combinations of EC, DMC, DEC and LiPF6, and contains no less than 10000 ppm of water; the baking temperature is 60-90°C, and the baking time is 4-6h.

[0014] In an optional embodiment, the cleaning is specifically washing by swinging in clean water for 2-5 minutes, followed by soaking in clean water for 30-60 minutes.

[0015] In an optional embodiment, the cast CPP film sample is a structure of a heat-sealing layer, a support layer and an adhesive layer stacked in sequence; the adhesive layer is maleic anhydride-modified polypropylene or maleic anhydride-modified polyethylene.

[0016] In an optional embodiment, the aluminum foil sample that is peeled off in step S3 and is not bonded to the cast CPP film sample is the aluminum foil sample on the side that is bonded to the heat-sealing layer of the cast CPP film sample.

[0017] The beneficial effect of the present invention is that the electrolyte resistance performance testing method of the aluminum-plastic film prepared by the thermal bonding process simulates the thermal bonding process of the aluminum-plastic film by partially heat-sealing the CPP and the aluminum foil, and there is no need to perform a complete thermal bonding of the aluminum-plastic film and then perform an electrolyte resistance test. In addition, the electrolyte resistance performance of the aluminum-plastic film can be known from the peel strength after the simulated enhanced electrolyte corrosion test, which can be effectively known in advance at the semi-finished product stage to avoid losses after mass production.

[0018] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.

[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 A schematic diagram of the structure of a sample strip provided in an embodiment of the present disclosure; Figure 2 Side view of a sample strip provided for embodiments of the present disclosure.

[0022] In the figure: 1. First aluminum foil sample; 2. Cast CPP film sample; 3. Second aluminum foil sample; 4. Local heat sealing area. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.

[0025] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0026] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.

[0027] Because the semi-finished CPP film roll and the semi-finished aluminum foil roll after passivation treatment have not been laminated, the electrolyte resistance of the laminated product cannot be detected in advance. The electrolyte resistance performance test of the aluminum-plastic film often occurs after the aluminum-plastic film is made into a finished product, and the test takes a long time. This delayed detection method makes potential quality problems discovered only after the product is mass-produced. And there is currently a lack of fast, efficient and accurate methods for pre-testing the electrolyte resistance performance of aluminum-plastic film suitable for thermal lamination process.

[0028] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.

[0029] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0030] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0031] The embodiment of the present disclosure provides a method for testing the electrolyte resistance performance of an aluminum-plastic film prepared by a thermal bonding process, comprising the following steps: step S1, cutting two passivated aluminum foil samples and one cast CPP film sample respectively; step S2, stacking the samples in the order of aluminum foil sample, cast CPP film sample, and aluminum foil sample and performing partial heat sealing to obtain a heat-sealed sample; step S3, quenching the heat-sealed sample, peeling off the aluminum foil sample that is not bonded to the cast CPP film sample, and then cutting the local heat-sealed area to obtain a sample strip; step S4, immersing the sample table in an electrolyte, sealing, storing, and baking, and then cooling and cleaning to obtain an electrolyte-treated sample strip; step S5, peeling off the aluminum foil sample and the cast CPP film sample in the electrolyte-treated sample strip, and testing to obtain the peeling force of the electrolyte-treated sample strip.

[0032] like Figure 1 and Figure 2 Specifically, the aluminum foil sample after the rapid cooling treatment in step S3 is as shown in Figure 1 As shown, Figure 1 The first aluminum foil sample 1 and the cast CPP film sample 2 exposed in the step are for easy observation of the layer structure after peeling off the upper layer; the sample strips in step S3 are as follows Figure 2 As shown, there are the first aluminum foil sample 1, the cast CPP film sample 2 and the second aluminum foil sample 3, respectively.

[0033] In some embodiments, specifically, the size of the aluminum foil sample and the cast CPP film sample is not less than 10 cm*10 cm.

[0034] In some embodiments, specifically, the aluminum foil sample includes a bright surface and a matte surface, and the bright surface of the aluminum foil sample is the contact surface with the cast CPP film sample.

[0035] In some embodiments, specifically, the thickness of the aluminum foil sample is 30-60 μm.

[0036] In some embodiments, specifically, the packaging temperature of the local heat seal is 130-250° C., the heat seal time is 2-10 s, the packaging pressure is 0.2-0.6 MPa, and the sealing head width is 10 mm.

[0037] In some embodiments, specifically, the rapid cooling method is to cool the heat-sealed sample between two iron plates for 5-10 s.

[0038] In some embodiments, specifically, the electrolyte includes any one or more combinations of EC, DMC, DEC and LiPF6, and contains no less than 10000 ppm of water; the baking temperature is 60-90°C, and the baking time is 4-6h.

[0039] In some embodiments, specifically, the cleaning is specifically washing in clean water with swing for 2-5 min, followed by soaking in clean water for 30-60 min.

[0040] In some embodiments, specifically, the cast CPP film sample is a structure of a heat-sealing layer, a support layer and an adhesive layer stacked in sequence; the adhesive layer is maleic anhydride-modified polypropylene or maleic anhydride-modified polyethylene.

[0041] In some embodiments, specifically, the aluminum foil sample that is not bonded to the cast CPP film sample and is peeled off in step S3 is the aluminum foil sample on the side that is bonded to the heat-sealing layer of the cast CPP film sample. In order to prevent the CPP from melting in direct contact with the seal head, the aluminum foil sample needs to be peeled off due to delamination without adhesion after heat sealing. Example 1

[0042] Step S1: Cut two 10cm*10cm passivated 40um aluminum foils and one 10cm*10cm cast CPP film with a cutter; Step S2: stacking the cut square samples according to the first aluminum foil sample, the cast CPP film sample and the second aluminum foil sample, with both sides of the CPP in contact with the bright side of the aluminum foil, and performing partial heat sealing at a packaging temperature of 200° C., a packaging time of 6 s, a packaging pressure of 0.4 MPa, and a sealing head width of 10 mm to form a partial heat sealing area; Step S3: The partially heat-sealed sample is rapidly cooled to 25° C. for 8 seconds, and the aluminum foil not bonded to the CPP layer is peeled off, and four independent sample strips are cut with a standard cutting knife; Step S4: Soak the cut sample strips in an electrolyte containing 10000ppm water, and seal them in an oven at 85℃ for 4 hours; the electrolyte is a mixture of EC:DMC:DEC=1:1:1 and containing 1mol / L LiPF6. After cooling to room temperature, take them out and put them in running clean water for 3 minutes, and then soak the samples in clean water for 30 minutes to clean them. Step S4: Take the cleaned specimen out of the clean water, wipe off the water, partially peel off the CPP layer and the aluminum layer, and use a tensile tester to test the peeling force of the CPP layer and the aluminum layer after electrolyte corrosion.

[0043] In this embodiment, specifically, EC is ethylene carbonate, DMC is dimethyl carbonate, and DEC is diethyl carbonate. Example 2

[0044] Repeat step S1, and stack the obtained cut square samples to form an aluminum-plastic film product and a battery, and observe the leakage for a long time under an environment of 25° C. and 50% RH.

[0045] Specifically, samples 1-4 were prepared according to the methods of Example 1 and Example 2, respectively, and the obtained test results are shown in Table 1 below.

[0046] Table 1

[0047] Specifically, when the electrolyte peeling resistance result tested according to the method of the present invention is greater than 5.5N / 10mm, it can be ensured that the battery made of the aluminum-plastic film after the CPP and the passivated aluminum foil are thermally bonded will not leak for eighteen months.

[0048] In summary, the electrolyte resistance test method of the aluminum-plastic film prepared by the thermal bonding process simulates the thermal bonding process of the aluminum-plastic film by partially heat-sealing the CPP and the aluminum foil. There is no need to perform a complete thermal bonding of the aluminum-plastic film before conducting an electrolyte resistance test. In addition, the electrolyte resistance of the aluminum-plastic film can be known from the peel strength after the simulated enhanced electrolyte corrosion test, which can be effectively known in advance at the semi-finished product stage to avoid losses after mass production.

[0049] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for testing the electrolyte resistance of an aluminum-plastic film prepared by a thermal bonding process, characterized in that: The steps include: Step S1, cutting two passivated aluminum foil samples and one cast CPP film sample respectively; Step S2, stacking the samples in the order of aluminum foil sample, cast CPP film sample, and aluminum foil sample and partially heat-sealing them to obtain heat-sealed samples; Step S3, quenching the heat-sealed sample, peeling off the aluminum foil sample that is not bonded to the cast CPP film sample, and then cutting the local heat-sealed area to obtain a sample strip; Step S4, immersing the sample stage in an electrolyte, sealing, storing, and baking, and then cooling and cleaning to obtain an electrolyte-treated sample strip; as well as Step S5, peeling off the aluminum foil sample and the cast CPP film sample in the electrolyte-treated sample strip, and testing to obtain the peeling force of the electrolyte-treated sample strip.

2. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The size of the aluminum foil sample and the cast CPP film sample is not less than 10 cm*10 cm.

3. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The aluminum foil sample includes a bright surface and a matte surface, and the bright surface of the aluminum foil sample is the contact surface with the cast CPP film sample.

4. The method for testing the electrolyte resistance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The thickness of the aluminum foil sample is 30-60 μm.

5. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The packaging temperature of the local heat seal is 130-250° C., the heat seal time is 2-10 s, the packaging pressure is 0.2-0.6 MPa, and the sealing head width is 10 mm.

6. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The rapid cooling method is to clamp the heat-sealed sample between two iron plates for cooling, and the cooling time is 5-10 s.

7. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The electrolyte comprises any one or more combinations of EC, DMC, DEC and LiPF6, and contains no less than 10000 ppm of water; The baking temperature is 60-90° C. and the baking time is 4-6 h.

8. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The cleaning specifically comprises swinging cleaning in clean water for 2-5 min, and then immersing cleaning in clean water for 30-60 min.

9. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 1, characterized in that: The cast CPP film sample is a structure of a heat-sealing layer, a support layer and an adhesive layer stacked in sequence; The adhesive layer is maleic anhydride modified polypropylene or maleic anhydride modified polyethylene.

10. The method for testing the electrolyte resistance performance of the aluminum-plastic film prepared by the thermal bonding process according to claim 9, characterized in that: The aluminum foil sample that is peeled off in step S3 and is not bonded to the cast CPP film sample is the aluminum foil sample on the side that is bonded to the heat-sealing layer of the cast CPP film sample.